Distributed Secondary Control with Consensus-Based Adaptive Droop and Voltage Observer for DC Microgrids - Khusnul Hidayat; Arif Nur Afandi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2026)
This paper proposes a fully distributed secondary control scheme for a low-voltage DC microgrid with ring topology. The main objectives are to restore the common bus voltage to its nominal reference and to achieve accurate proportional current sharing among distributed generator units in the presence of non-uniform line resistances and mixed load conditions. The proposed secondary layer integrates a consensus-based adaptive droop controller and a consensus-based voltage observer. The adaptive droop mechanism dynamically adjusts the virtual impedance of each converter using neighbor-to-neighbor current information to reduce current-sharing errors, while the voltage observer provides a distributed estimate of the average bus voltage to compensate for droop-induced voltage deviations. The effectiveness of the proposed method is validated through simulation on a ring-configured DC microgrid consisting of four converters and five buses. A comparative study demonstrates that conventional droop control improves current sharing but introduces significant steady-state voltage deviation. By contrast, the proposed integrated approach achieves nearly zero current-sharing error while maintaining the DC bus voltage close to its reference value. The dynamic performance is further evaluated under both resistive-load and constant-power-load variations. The results show that the controller ensures fast voltage restoration, accurate proportional current sharing, and stable operation without sustained oscillations, even under nonlinear constant-power-load conditions. These findings indicate that the proposed distributed secondary control strategy provides robust voltage regulation and precise current sharing for ring-type DC microgrids.